Metabolically healthy obese individuals present similar chronic inflammation level but less insulin-resistance than obese individuals with metabolic syndrome - Penas Steinhardt, Alberto (2020)
Fil: Penas Steinhardt, Alberto. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.